A human thermal balance based evaluation of thermal comfort subject to radiant cooling system and sedentary status. (25th July 2017) - Gao, S.; Li, Y.; Wang, Y.A.; Meng, X.Z.; Zhang, L.Y.; Yang, C.; Jin, L.W.
Highlights: The relation of thermal comfort and thermal balance between human body and surroundings is explored. PMV model is simplified with the sensible heat loss from human body. Human thermal comfort could be evaluated from thermal balance instead of environmental factors. It is noted that sensible heat loss from human body is approximately linear with PMV. Correlation between PPD and sensible heat loss from human body is developed. Abstract: The radiant cooling air conditioning system has been increasingly prevailed, due to its features of maintaining more comfortable indoor environment with lower energy consumption against the conventional cooling methods. This work explores the effect of heat exchange between human body and surroundings on human thermal comfort subject to the radiant cooling air conditioning system. The widely accepted thermal comfort index, PMV (Predicted Mean Vote), is adopted to evaluate human thermal comfort. To determine the heat loss from human body, the human thermal balance and heat release characteristics are discussed. The test room with various boundary conditions are simulated and analyzed by Airpak. It is found that for sedentary human body subject to the radiant cooling system, the sensible heat loss is approximately linear to the PMV and the value of sensible heat loss for the thermal neutrality (PMV = 0) is a constant. The simplified PMV model is finally achieved based on the results obtained from 594 calculated points. In addition, the relation between the sensible heat loss and the PPD (Predicted Percentage of Dissatisfied) is obtained. The findings from this work could be referenced for thermal comfort evaluation and system design when radiant cooling applies.